Theoretical and Practical Engagement of Different Religious Traditions in Climate Issues - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2016)
This article sets itself the goal of presenting a variety of religious activities to protect the climate. It adopts the assumption that – as it seems – was able to confirm that the encyclical Laudato Si’ was the kind of catalyst that has mobilized and activated the different religious traditions around the world to actively joined in climate protection in the perspective of upcoming climate conference COP21 in Paris. The distinction present in Western thought between theoretical and practical human activity is a reference to show the various climate initiatives of religions, which took place since publication of the encyclical Laudato Si’ until the climate summit in Paris. The essay distinguished three main points: 1. Experience of the ecological crisis. 2. Reflection of the ecological crisis and its diagnosis. 3. Attempts to overcome the crisis. The author focuses mainly on step third pointing to various practical initiatives of different religious traditions, especially Christianity, Buddhism, Hinduism, Islam, the indigenous religions, the Baha’i faith and common, interreligious climate initiatives.